MEDIA MASSA SEBAGAI SARANA DAKWAH YANG STRATEGIS DALAM KONTRA TERORISME MEDIA BARAT DAN YAHUDI - Islam, Nur (BINA' AL-UMMAH, 2015)
Western and Jews mass media creates 11 September 2001 WTC and Pentagon bombing tragedy as a point of departure of new propaganda and terror against Islam and its adherents. Western and Jews media have massively framed and labelled Islam and its adherents as terrorists, ever since this tragedy occurred. Sophistication, seriousness and professionality of Western and Jews mass media disempowers Muslims in confronting their information attack. Their mass media negatively frames and undermine Islamic teachings. Massive and systemic Western and Jews propaganda and hegemony which are distant from journalism ethics have to be confronted by Muslims through journalistic jihad, that is, dakwah bi al-qalam as contra terrorism through mass media. Dakwah bi al-hikmah and mauizhah hasanah through mass media has to be performed by Muslims individuals, institutions and organisations in smart, interesting, creative manner. Furthermore, the contents of dakwah through print and electronic mass media have to explain to audience that Islam is not terrorist religion. Rather, Islam is peaceful, and benevolent religion respecting others for the sake of happiness both in world and hereafter